ä½¿ç”¨ç¬”é¡ºæ•™å¦æé«˜åˆä¸åœ£çˆ¶å¦æ ¡äºŒå¹´çº§å¦ç”Ÿçš„æ±‰å—ä¹¦å†™èƒ½åŠ› - Veronica, Yessi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
AbstractChinese characters are composed of strokes. There are some fixed orders in strokes when writing Chinese characters. The order of writing Chinese characters is called stroke orders. Writing Chinese characters cannot be arbitrary, and to comply with certain rules of stroke, so as to write correctly and beautifully. To write Chinese characters, it is a must to master strokes, stroke orders, and Chinese characters structure. Students of Junior High School found it difficult in writing Chinese characters so they wrote it carelessly. In order to improve the students ability in writting Chinese characters, the writer implied the "Stroke Order Teaching Method" for 8th grade Students on class C and D in Bruder Junior High School Pontianak by conducting experimental research. After doing the research, the writer concluded that the students’ has mastery of Chinese characters strokes, strokes orders and Chinese structure has reached more than 70%, in percentage while the ability in writing Chinese characters is in 66.63%. The writer hopes this thesis can be useful as the references for the Chinese subject teachers to conducts classroom teaching activities. Keywords: Teaching of Chinese Characters, Writing Chinese Characters, Writing Strokes